« On est encore en vie, à la grande surprise de tout le monde… » L’expérience des personnes âgées trans vivant avec une démence dans une société âgiste, cisgenriste et cogniticiste - Alexandre Baril; Marjorie Silverman (Glad!)
Trans and non-binary older adults living with dementia experience forms of marginalization, pathologization, and discrimination embedded in epistemic violence that leads them to be mistreated and dismissed as knowledgeable subjects. Based on empirical findings from a Canadian study examining the experiences of trans and non-binary people living with dementia and their carers, we combat this epistemic violence by focusing on the first-hand narratives of this population and their carers. Narrative interviews were conducted with six participants (N= 6): four carers of trans and non-binary adults living with dementia and two trans (binary) people living with dementia. Through a thematic analysis, we examine the unique aspects of living with dementia as a trans or non-binary person. First, the findings show how cogniticism impacts the experience of gender identity and cisgenderism, for example through blocked surgeries, excessive gatekeeping, and not being taken seriously by practitioners. Second, the findings discuss how dementia impacts gender identity and cisgenderism, for example, by increasing the need for formal care that can in turn increase vulnerability to structural violence. Third, the findings illustrate how cisgenderism and gender identity impact the experience of dementia and cogniticism, for example by limiting care options and the ability to advocate for oneself. Fourth, the findings highlight the silo mentality among practitioners, since most of them do not work with an intersectional lens. The article concludes by offering recommendations.